Integrity plan - Fedran, Jasna (Lex localis, 2018)
Corruption is a society disease necessitating a preventive approach. As it is both a national and a local issue, its treatment must be facilitated through national and local efforts. In view of the fact that the best remedy against it is integrity, this paper focuses on the concept of integrity plan, revealing the results of the thereto-related implementation efforts in the Slovenian public sector after the 2nd deadline for integrity plan submission. In general, integrity plan was acknowledged as a useful preventive anti-corruption measure well accepted by the state authorities but less by the local ones.
Keywords: corruption; korupcija; načrt integritete; integrity plan; javna uprava; public sector; state and local authorities; državni in lokalni organi; komisija za preprečevanje korupcije; Commission for the prevention of corruption